Implementation of Canva Application as Digital Learning Media in Influencing Student Creativity Skills - Abin, Mildah Rochmatul Laili; Praja Dewi Juniar, Tri; Ibadil Maula, Farij; Pahlevi, Triesninda (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2023)
The purpose of this research is to determine the effect of using Canva application as a digital learning media on the creativity skills of students of Office Administration Education Study Program, Surabaya State University. This research is a type of quantitative research with a comparative causal method (ex-post facto). Determination of the number of research samples was carried out in accordance with the Slovin equation involving 95 students of the Office Administration Education Study Program Class of 2022. The data analysis technique uses simple linear regression with the help of SPSS 16 for windows software. The results showed that the simple regression coefficient was positive at 0.572. The higher the level of use of the Canva application as a digital learning media, the more student creativity skills increase. The R Square value of 0.406 means that the variable use of the Canva application affects the student's creativity skills by 40.6%.